Climate and trade policy bottom-up approaches towards global agreement - Carraro, Carlo; Egenhofer, Christian, 1960-; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2007)
The difficulty of achieving and implementing a global climate change agreement has stimulated a wide range of policy proposals designed to favour the participation of a large number of countries in a global cooperative effort to control greenhouse gas emissions. This significant book analyses the viability of controlling climate change through a set of regional or sub-global climate agreements rather than via a global treaty.
Bottom-up approaches towards a global climate agreement : an overview -- Carlo Carraro, Christian Egenhofer and Noriko Fujiwara -- Regional and subglobal climate blocs : a cost-benefit analysis of bottom-up climate regimes / Barbara Buchner and Carlo Carraro -- Do regional integration approaches hold lessons for climate change regime formation? : the case of differentiated integration in Europe / Noriko Fujiwara and Christian Egenhofer -- Trade, the environment and climate change : multilateral versus regional agreements / David Kernohan and Enrica De Cian -- Participation incentives and technical change : from top-down to bottom-up climate agreements / Barbara Buchner and Carlo Carraro -- Bottom-up approaches to climate change control : some policy conclusions / Carlo Carraro and Christian Egenhofer.
Includes bibliographical references and index.
Keywords: Environmental policy; Commercial policy; Pollution -- Economic aspects; Climatic changes -- Economic aspects; Electronic books